The Research of Knowledge about the Joint Protection for Persons with Rheumatoid Arthritis (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2014)
Research background. According to the statistics, every fourth resident of Lithuania complains of rheumatic malaise. Rheumatoid arthritis is the most serious disorder of rheumatic diseases. Reduced joint flexibility, joint deformities, and the surrounding muscles atrophy is one of the worst effects of RA. They affect self-care, productivity and leisure activities of the persons. For these reasons it is crucial for the persons with rheumatoid arthritis to be aware of possible harmful and dangerous aspects of their e daily life activities as well as the necessity of self-dependence. The aim of the research was to evaluate the knowledge of persons with rheumatoid arthritis about the joint protection during the exacerbations and remissions of the disease. Methods. The research involved 30 Kaunas city “Arthritis” club members with rheumatoid arthritis. Average age of respondents was 69.9 ± 0.9 years. The study was supported by a questionnaire, which included 29 questions. In order to protect their privacy, the patients were interviewed anonymously. Results. The research results showed which joint protection principles were best know and worst by the patients with RA. The study provided data about the behaviours of respondents in daily life activities protecting their joints of disease exacerbation and remission. Conclusions. It became clear that patients with rheumatoid arthritis had little knowledge about the possible ways of substitution of the injured joints, work and relaxation regimens, preservation of energy, joint mobility and stability and the use of technical rehabilitation devices. Persons with rheumatoid arthritis often avoided various activities during the exacerbation of the disease as well as they did not take care of their joints during the remission of the disease.Keywords: rheumatoid arthritis, joint protection, occupational therapy.